Ca6.5Pb1.5ZnBi(VO4)7, a novel whitlockite-type vanadate: crystal structure refinement and properties characterization. Issue 3 (24th July 2017) - Petrova, Daria; Deyneko, Dina; Stefanovich, Sergey; Aksenov, Sergey; Lazoryak, Bogdan
Abstract : Novel compounds Ca8− x Pb x ZnBi(VO4 )7 (0 ≤ x ≤ 1.5) solid solution with the whitlockite-type structure were synthesized by a standard solid-state method. The unit-cell parameters were determined by X-ray powder diffraction and using Le Bail decomposition. The crystal structural of Ca6.5 Pb1.5 ZnBi(VO4 )7 was refined by Rietveld method. It is found that Pb 2+ cations occupy a half of the M 3 site, whereas the M 1 and M 2 sites are predominantly occupied by calcium with admixture of Bi 3+ cations. The M 5 site is fully occupied by Zn 2+ cations. The M 4 site in the structure of studied sample remains vacant and does not participate in the cations arrangement. Optical second harmonic generation demonstrates high non-linear optical activity. Dielectric investigations confirm polar space group R 3 c . Changes in the non-linear optical and ferroelectric parameters are matched with lead and zinc cation distribution over the sites of the whitlockite-type structure.